DAMPAK PERCERAIAN ORANG TUA TERHADAP KESEHATAN PSIKOLOGIS REMAJA DI DESA KEBONDALEM KABUPATEN PEMALANG JAWA TENGAH - Dwiningthyas, Maria Evelyne Ruth; Ides, Stefanus Andang; Anggraeni, Lina Dewi (Journal Healthcare Education, 2024)
Divorce is the termination of marital status by a judge's decision upon the request of one party in the marriage. The impact of divorce on teenagers, if not addressed immediately, can lead to depression in children, arising from their lack of mental preparedness to accept the reality of their parents' separation. This study aims to dig deeper into the Impact of Parental Divorce on the Psychological Health of Adolescents in Kebondalem Village, Pemalang, Central Java. This study used a qualitative method with a phenomenological descriptive qualitative research design. The number of participants was 8 teenagers aged 17-18 years whose parents had been divorced for 5 years. Data obtained by in-depth interviews and colaizzi analysis. This research produced five themes, namely the meaning of family for children's lives, emotional changes felt, feelings of burden and discrimination from others, the disadvantage of having a harmonious family, and the impact experienced by children from divorce.